Expo Centre, Vancouver, B.C., Canada - Jurgen Vogt::::::::: (Agency Press)
Opening May 2, 1985, one full year before Expo 86, Expo Centre is more than a taste of Expo 86. It's an entire experience all on its own. A visit here will take you to an exhibition hall of the future with the latest in computer graphics and a kinetic light sculpture. Three theatres take you on visual voyages you'll never forget. Also included in this geodesic sphere is an amazing scale model of the entire exposition site. Expo Centre is unlike anything you've ever experienced before.